IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU PASAL 6 NOMOR 12 TAHUN 2008 TENTANG PENERTIBAN SOSIAL ORANG DENGAN GANGGUAN JIWA (ODGJ) DI PEKANBARU - Ilham Rizki Pratama; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
People with ordinary mental disorders in short (ODGJ) can be said to be mentally handicapped because a disability means a deficiency that causes a value or quality is not good or imperfect (which is found in the body, objects, mentality or morals), whereas mentality is concerned with the mind and character humans, who are not body or energy. Then if we see the meaning of